Harnessing the potential of African youth for transforming health research in Africa - Yusuff Adebayo Adebisi; Nafisat Dasola Jimoh; Archibong Edem Bassey; Hassan Olayemi Alaka; Mohamed Marah; Chimwemwe Ngoma; Isaac Olushola Ogunkola; Oumnia Bouaddi; Idahor Courage; Radwa Abdalla Abdelatif El-Abasiri; Rime Boutahar; Molly Unoh Ogbodum; et al. (BMC, 2024)
Abstract Africa faces a significant burden of infectious diseases, including Malaria and HIV/AIDS, along with an increasing prevalence of non-infectious diseases such as diabetes and cancer. This dual health challenge is amplified by socioeconomic difficulties, restricted access to healthcare, and lifestyle changes, thus present unique scientific needs. Effectively addressing these issues requires a skilled scientific workforce adept in comprehensive healthcare strategies. This analysis explores the critical landscape of health research in Africa, emphasizing the unique opportunity presented by the continent's youthful population, projected to reach almost 1 billion by 2050. The youth's innovative potential and fresh perspectives offer a chance to overcome development barriers in health research. Nevertheless, challenges such as under-resourced education, limited research training, inadequate mentorship, and funding difficulties persist. This paper urgently calls upon African leaders, international partners, and stakeholders to prioritize health research, mobilize funding, forge strategic partnerships, and empower the youth as essential steps to capitalize on the continent's dynamic youth for breakthrough health outcomes. Such investments are vital not just for health but for the overall economic, social, and strategic growth of the continent. Through shared responsibility and a united effort, the potential of African youth can be harnessed, leading to transformative research, improved health outcomes, and a prosperous future. This perspective represents the collective voice of passionate young researchers and advocates across Africa, calling for a new era of health research on the continent.